Medical education during Covid-19 pandemic - it is time to embrace the new norm - Omar, Ahmad Marzuki; Md Nor, Azmi (International Islamic University Malaysia, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has affected the socio-economic fabric of the society globally. Educational institutions, including medical schools are no exception. It has caused wide-spread disruption to teaching and learning (T&L) activities and may impact the future of medical education worldwide.